2009
DOI: 10.1007/s10792-009-9302-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in the retinal pigment epithelium on spectral-domain OCT in the unaffected eyes with idiopathic central serous chorioretinopathy

Abstract: Spectral-domain optical coherence tomography showed morphologic alterations in retinal pigment epithelium in both eyes of patients with idiopathic central serous chorioretinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 28 publications
3
30
1
2
Order By: Relevance
“…However, it has been reported in an en face OCT study that it was detected in 35 % of the eyes with acute CSCR [19]. Additionally, RPE layer mapping study using OCT demonstrated that RPE bulging was in 94% of asymptomatic eyes in patients with CSR [25]. RPE bulging was observed in all of the females and a percent of 87.5 in males in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…However, it has been reported in an en face OCT study that it was detected in 35 % of the eyes with acute CSCR [19]. Additionally, RPE layer mapping study using OCT demonstrated that RPE bulging was in 94% of asymptomatic eyes in patients with CSR [25]. RPE bulging was observed in all of the females and a percent of 87.5 in males in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…In the setting of unilateral classic CSC, other authors have alluded to similar forme fruste findings without serous neurosensory detachment in the fellow eye, including pigmentary changes, 17 asymptomatic PEDs, 18,19 choroidal hyperpermeability, vascular dilation, and increased choroidal thickness. 3,5 These reports suggest the presence of a limited CSC variant that may or may not precede the development of the serous macular detachment of classic CSC.…”
Section: Discussionmentioning
confidence: 99%
“…Using Fourier domain OCT, Fujimoto et al [8] demonstrated an RPE defect within the PED at a leakage site through which fluid might escape from the sub-RPE space into the subretinal space [8]. In the series described by Gupta et al [26], 94% of the CSR patients showed evidence of RPE bumps and 11.8% had PEDs [26]. …”
Section: Discussionmentioning
confidence: 99%